2009
DOI: 10.1021/bc9000245
|View full text |Cite
|
Sign up to set email alerts
|

18F, 64Cu, and 68Ga Labeled RGD-Bombesin Heterodimeric Peptides for PET Imaging of Breast Cancer

Abstract: Radiolabeled RGD and bombesin (BBN) radiotracers that specifically target integrin αvβ3 and gastrin releasing peptide receptor (GRPR) are both promising radiopharmaceuticals for tumor imaging. We recently designed and synthesized a RGD-BBN heterodimeric peptide with both RGD and BBN motifs in one single molecule. The 18F-labeled RGD-BBN heterodimer exhibited dual integrin αvβ3 and GRPR targeting in a PC-3 prostate cancer model. In this study we investigated whether radiolabeled RGD-BBN tracers can be used to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
143
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(145 citation statements)
references
References 44 publications
1
143
0
1
Order By: Relevance
“…One major advantage of heterodimer over the corresponding monomers is the multivalency effect, resulting in improved binding affinity and increased number of effective receptors (20,(22)(23)(24). Consistently, both 68 Ga-BBN-RGD and 68 Ga-BBN showed uptake in the primary prostate tumors that were either GPRR-positive or integrin a v b 3 -positive.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…One major advantage of heterodimer over the corresponding monomers is the multivalency effect, resulting in improved binding affinity and increased number of effective receptors (20,(22)(23)(24). Consistently, both 68 Ga-BBN-RGD and 68 Ga-BBN showed uptake in the primary prostate tumors that were either GPRR-positive or integrin a v b 3 -positive.…”
Section: Discussionmentioning
confidence: 72%
“…In a PC3 xenograft model, 18 F-FB-BBN-RGD had significantly higher tumor uptake than monomeric RGD and monomeric BBN peptide tracer analogs at all time points examined (20). A series of preclinical studies using the same strategy have confirmed several advantages of heterodimers including increased number of effective receptors, improved binding affinity, and pharmacokinetics (20,(22)(23)(24).…”
mentioning
confidence: 86%
“…This approach was chosen by different groups (38)(39)(40). The preferred "coligand" was the a V b 3 -targeting RGD motif.…”
Section: Development Of Heterobivalent Ligands With Short Linkersmentioning
confidence: 99%
“…
molecules that are highly expressed in tumor vasculature [11] are widely used to image breast, [15] brain, [16] and lung [17] cancers in small animal models; however, RGD peptides often provide poor imaging contrast because the integrins are also expressed on other endothelial cells. The RGD peptides act as "strongly" interacting integrin ligands that nonselectively bind to the various integrins and are rapidly captured by the cells via receptor-mediated endocytosis, which decreases the tumor/ background signal ratio.

While most studies have focused on optimizing ligands with a high affinity and selectivity to the cell surface targets, we envisioned a new imaging approach that utilized one high-and one low-affinity ligand targeted to independent receptors on a target cell surface.

…”
mentioning
confidence: 99%